The Preschool Confusion Assessment Method for the ICU: Valid and Reliable Delirium Monitoring for Critically Ill Infants and Children*. Issue 3 (March 2016) - Smith, Heidi A. B.; Gangopadhyay, Maalobeeka; Goben, Christina M.; Jacobowski, Natalie L.; Chestnut, Mary Hamilton; Savage, Shane; Rutherford, Michael T.; Denton, Danica; Thompson, Jennifer L.; Chandrasekhar, Rameela; Acton, Michelle; Newman, Jessica; et al.
Abstract : Objectives: Delirium assessments in critically ill infants and young children pose unique challenges due to evolution of cognitive and language skills. The objectives of this study were to determine the validity and reliability of a fundamentally objective and developmentally appropriate delirium assessment tool for critically ill infants and preschool-aged children and to determine delirium prevalence. Design and Setting: Prospective, observational cohort validation study of the PreSchool Confusion Assessment Method for the ICU in a tertiary medical center PICU. Patients: Participants aged 6 months to 5 years and admitted to the PICU regardless of admission diagnosis were enrolled. Measurements and Main Results: An interdisciplinary team created the PreSchool Confusion Assessment Method for the ICU for pediatric delirium monitoring. To assess validity, patients were independently assessed for delirium daily by the research team using the PreSchool Confusion Assessment Method for the ICU and by a child psychiatrist using the Diagnostic and Statistical Manual of Mental Disorders criteria. Reliability was assessed using blinded, concurrent PreSchool Confusion Assessment Method for the ICU evaluations by research staff. A total of 530-paired delirium assessments were completed among 300 patients, with a median age of 20 months (interquartile range, 11–37) and 43% requiring mechanical ventilation. The PreSchool Confusion Assessment Method for the ICU demonstrated a specificity of 91% (95% CI, 90–93), sensitivity of 75% (95% CI, 72–78), negative predictive value of 86% (95% CI, 84–88), positive predictive value of 84% (95% CI, 81–87), and a reliability κ–statistic of 0.79 (0.76–0.83). Delirium prevalence was 44% using the PreSchool Confusion Assessment Method for the ICU and 47% by the reference rater. The rates of delirium were 53% versus 56% in patients younger than 2 years old and 33% versus 35% in patients 2–5 years old using the PreSchool Confusion Assessment Method for the ICU and reference rater, respectively. The short-form PreSchool Confusion Assessment Method for the ICU maintained a high specificity (87%) and sensitivity (78%) in post hoc analysis. Conclusions: The PreSchool Confusion Assessment Method for the ICU is a highly valid and reliable delirium instrument for critically ill infants and preschool-aged children, in whom delirium is extremely prevalent.